The Realization of Interactive Television Services - Du Baichuan (Tongxin xuebao)
in this paper,the eminent role of CATV networks in the development of China’s Information Superhighway is pointed out,while limitted role will be revealed for the development of interactive television in telephone networks;the key techniques of terminal interactive services and bi-directional transmission of interactive services,as well as certain way of receiving（i.e.integrated receiver/decoder,IRD）,are briefly introduced ;and possoble development of network structures and information working platforms,such as MPEG-2,are also discussed.